Synthesis and characterization of zinc oxide/graphene (ZnO/Gn) on titanium dioxide/niobium pentoxide (TiO₂/Nb₂O₅) thin film for methylene blue removal / Wan Marhaini Wan Harrum - Wan Harrum, Wan Marhaini (2023)
The existing challenges associated with the efficacy of TiO₂/ZnO thin films for photocatalytic wastewater treatment, including complex and costly seed layer coating methods, low photocatalytic efficiency, the removal of toxic compounds, and interfacial layer mismatch with ZnO and other elements, necessitate further investigation. This study aims to address these issues by depositing thin film samples of TiO₂-ZnO, optimising the parameters of graphene (Gn) (including atomic percentage, annealing, and immersion temperatures) in TiO₂-ZnO/Gn, and investigating the effects of incorporating 5 atomic percent of Nb₂O₅ into TiO₂-ZnO/Gn samples. In addition, it intends to assess the methylene blue removal on TiO₂-ZnO, TiO₂-ZnO/Gn, and TiO₂/Nb₂O₅-ZnO/Gn. Graphene-based materials excel in energy harvesting and water splitting, outperforming commercial standards in photocatalysis and treatment, thus, the addition of Gn helps to enhance methylene blue adsorption. Besides, it is added to reduced electron-hole pair recombination rate and band gap narrowing. Addition of 5 at. % Nb₂O₅ to the TiO₂-ZnO/Gn nanocomposite regulates electron behaviour, reducing recombination and improving photodegradation. The seed layer was applied to glass substrates through the sol-gel spin coating method, while ZnO/Gn was synthesised via the solution-immersion technique. The optimisation process involved varying Gn atomic percentages (11 at. %, 13 at. %, 15 at. %, 17 at. %, and 19 at. %), solution immersion temperatures (70ºC, 80ºC, and 90ºC), and annealing temperatures (400ºC, 450ºC, 500ºC, 550ºC, and 600ºC) for TiO₂-ZnO/Gn samples. 5 at. % Nb₂O₅ was introduced as a dopant in the TiO₂ seed layer and integrated into the optimised TiO₂ZnO/Gn samples. Characterization techniques, including FESEM-EDX, XRD, HRTEM, and UV-Vis, were employed to assess morphological, structural, and optical properties. FESEM images confirmed the presence of Gn nanosheets and ZnO nanorods on the thin film, exhibiting distinctive grain-like structures in TiO₂/Nb₂O₅-ZnO/Gn. EDX analysis confirmed the materials present. X-ray diffraction analysis indicated crystallinity, with hexagonal wurtzite nanorods (prominent peaks at planes 100, 002, and 101), anatase TiO₂ (plans 101 and 200), Nb₂O₅ (plane 102), and Gn (plane 002) identified on the glass substrate. The HRTEM SAED patterns verified the crystal planes of the TiO₂, Nb₂O₅, ZnO, and Gn phases. The optimisation results identified 15 at.% Gn, 90°C solution immersion temperature, and 500°C annealing temperature as the optimised parameters for methylene blue removal. UV-Vis absorbance revealed that TiO₂/Nb₂O₅-ZnO/Gn exhibited the highest absorbance spectra, shifting towards visible light wavelengths. The energy band gap of TiO₂/Nb₂O₅-ZnO/Gn decreased from 3.0 eV to 2.6 eV. TiO₂/Nb₂O₅-ZnO/Gn demonstrated the highest degradation efficiency at 50.29%, outperforming TiO₂-ZnO/Gn (28.44%) and TiO₂-ZnO (29.66%). Collectively, TiO₂/Nb₂O₅-ZnO/Gn emerges as the most promising methylene blue removal.